Financial Inclusion, Digital Financial Inclusion and Air Quality: Evidence from Asian Countries - Linghui, Yang; Ming, Kelvin Lee Yong; Malan, Irfah Najihah Binti Basir; Yi, Shen; Soon, Ling Pick; Leong, Lin Woon (International Journal of Energy Economics and Policy, 2024)
Financial inclusion enables greater access to financial resources and facilitates green energy investments, thus emerging as a potential avenue to mitigate pollution. However, the relationship between financial inclusion and environmental impact is complex, with arguments both for and against its positive effects. This study aims to examine the impact of financial inclusion and digital financial inclusion on air quality in thirteen selected Asian countries. The dependent variables used in this study was the Air Quality Index (AQI). The independent variables were financial inclusion, digital financial inclusion, population growth, net trade of goods and services and gross domestic product (GDP). The findings showed that the proxies of financial inclusion had mix effects on air quality, while a higher level of digital financial inclusion led to a better air quality in Asian countries. This study also revealed that population growth and GDP may somehow affect the air quality of Asian countries as well. These results suggest that Asian countries with lower level of financial inclusion and digital financial inclusion need to improve their citizen’s access to financial resources. Several policies shall be implemented to enhance the level of financial inclusion and the air quality.